Uganda Country Assistance Evaluation, 2001-2007 : Joint IEG/OPEV Country Assistance Evaluation - Independent Evaluation Group (Washington, DC: World Bank, 2015)
The World Bank’s assistance strategies showed strong client orientation and were aligned with Uganda’s poverty reduction strategy. The programs were substantially effective in decentralization, public sector reform, growth and economic transformation, education, and water and sanitation. However, more could have been done to help counter the perception of increasing corruption, improve power supply, reduce transport costs, enhance agricultural productivity, and help with family planning and reproductive health. The AfDB’s assistance was also relevant and aligned with the government’s development goals. Its support substantially achieved its objectives for decentralization, public sector finance, growth and economic transformation, improved competitiveness, agriculture, and water and sanitation, as well as education and health. However, there were some shortcomings in the assistance provided for power and roads and in reducing corruption. This report evaluates World Bank and African Development Bank assistance to Uganda during 2001-07. The motivation to undertake a joint evaluation was the shift to a common strategic framework, the Uganda Joint Assistance Strategy (UJAS), to guide the formulation and delivery of their programs. Under a common strategic framework joint evaluation is, in principal, more cost effective than the equivalent separate evaluations, since at least some aspects of the evaluation can be done together. This also helps to reduce government transaction costs. The evaluation discusses the outcome of the support of each bank, rates each independently, noting that the two banks are of different size, capacity, and institutional setting. In addition, the two banks have programs that were not implemented jointly but in parallel, although they regularly engaged with one another as development partners. The outcome ratings for the two institutions are therefore not comparable and should not be used to imply that one institution did ‘better’ than the other.